2013
DOI: 10.4103/0974-620x.116622
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve hypoplasia

Abstract: Optic nerve hypoplasia (ONH) is a congenital anomaly of the optic disc that might result in moderate to severe vision loss in children. With a vast number of cases now being reported, the rarity of ONH is obviously now refuted. The major aspects of ophthalmic evaluation of an infant with possible ONH are visual assessment, fundus examination, and visual electrophysiology. Characteristically, the disc is small, there is a peripapillary double-ring sign, vascular tortuosity, and thinning of the nerve fiber layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
1
31
0
2
Order By: Relevance
“…The pathophysiology of ONH is unknown; however, its aetiology has been linked to several maternal risk factors making an accurate gestational history extremely important. Associations that are relevant in this case report include young maternal age, primiparity, maternal smoking and gestational diabetes 2. Additional associations include maternal use of alcohol, recreational drugs, anti-depressants, anti-convulsants and anti-emetics 2…”
Section: Descriptionmentioning
confidence: 90%
See 1 more Smart Citation
“…The pathophysiology of ONH is unknown; however, its aetiology has been linked to several maternal risk factors making an accurate gestational history extremely important. Associations that are relevant in this case report include young maternal age, primiparity, maternal smoking and gestational diabetes 2. Additional associations include maternal use of alcohol, recreational drugs, anti-depressants, anti-convulsants and anti-emetics 2…”
Section: Descriptionmentioning
confidence: 90%
“…This finding appears as a pale white/yellow ring around the optic disc, which is thought to represent the scleral canal 2. The ratio of disc diameter to disc–macula distance (measured from the temporal edge of the disc to the central fovea) is useful in determining the severity of the hypoplasia.…”
Section: Descriptionmentioning
confidence: 99%
“…In children whose mothers drank alcohol there are functional difficulties that are difficult to diagnose and classify, and often sensory integration dysfunction. For these children SI therapy is necessary and effective [10][11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. This work, because of the breadth of statistical analysis, only shows the effects of SI therapy on gross motor function.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,18 To date, the potential of SD OCT to assess optic nerve and macula morphology in patients with ONH in vivo has been largely unexplored. In 2013, Moon and Park 16 confirmed previous histopathology data in 1 patient with ONH compared with the healthy eye using SD OCT.…”
Section: Discussionmentioning
confidence: 99%
“…19 Provis at al 20 investigated the number of axons of the human fetal optic nerve and found that at least 70% regress during pregnancy. These findings led Mosier et al 12 and other investigators 14,18 to propose the hypothesis that ONH is the result of excessive RNFL regression. McCulley et al 21 suggested that ONH may be the result of retrograde RNFL degeneration from axons not proceeding into the contralateral tract at the chiasm.…”
Section: Optic Nerve Head Changesmentioning
confidence: 99%